The Marketing Research Process / Third Edition - Crimp Margaret (Prentice Hall, 1990)
This book explores the impact of technological developments, such as laser scanning, access to data banks via microcomputers, and the use of VDUs and microcomputers to collect and analyze data. Acknowledgements, An Introduction to the Marketing Research Process, Exploring the Market, Describing Markets: Design Choices, Describing Markets: Focus on Sampling, Describing Markets: Collecting Data by Means of Questions, Market Segmentation, Developing a Branded Product or Service, Establishing the Brand Identity and Pre-Testing the Whole, Conveying the Brand Message: Media Planning, Out in the Open: The Final go/ no-go decision, Evaluating Performance: What if we...? and Prediction, Index.